More in hope than expectation: a systematic review of women's expectations and experience of pain relief in labour - Joanne Lally; Madeleine J. Murtagh; Sheila Macphail; Richard Thomson (2008)
Childbirth is one of the most painful events that a woman is likely to experience, the multi-dimensional aspect and intensity of which far exceeds disease conditions. A woman's lack of knowledge about the risks and benefits of the various methods of pain relief can heighten anxiety. Women are increasingly expected, and are expecting, to participate in decisions about their healthcare. Involvement should allow women to make better-informed decisions; the National Institute for Clinical Excellence has stated that we need effective ways of supporting pregnant women in making informed decisions during labour. Our aim was to systematically review the empirical literature on women's expectations and experiences of pain and pain relief during labour, as well as their involvement in the decision-making process. A systematic review was conducted using the following databases: Medical Literature Analysis and Retrieval System Online (MEDLINE), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Bath Information and Database Service (BIDS), Excerpta Medica Database Guide (EMBASE), Midwives Information and Resource (MIDIRS), Sociological Abstracts and PsychINFO. Studies that examined experience and expectations of pain, and its relief in labour, were appraised and the findings were integrated into a systematic review. Appraisal revealed four key themes: the level and type of pain, pain relief, involvement in decision-making and control. Studies predominantly showed that women underestimated the pain they would experience. Women may hope for a labour free of pain relief, but many found that they needed or benefited from it. There is a distinction between women's desire for a drug-free labour and the expectation that they may need some sort of pain relief. Inaccurate or unrealistic expectations about pain may mean that women are not prepared appropriately for labour. Many women acknowledged that they wanted to participate in decision-making, but the degree of involvement varied. Women expected to take control in labour in a number of ways, but their degree of reported control was less than hoped for. Women may have ideal hopes of what they would like to happen with respect to pain relief, control and engagement in decision-making, but experience is often very different from expectations. Antenatal educators need to ensure that pregnant women are appropriately prepared for what might actually happen to limit this expectation-experience gap and potentially support greater satisfaction with labour.